Les Mémoires en vrac de Jean Ajalbert ou vers une (re)composition de la mémoire fin-de-siècle - Opiela-Mrozik, Anna Maria (Romanica Silesiana, 2024)
The article analyzes Memoires en vrac by Jean Ajalbert, a forgotten poet and writer at the turn of the 19th and 20th centuries, in the context of the functioning and creation of memory about the fin de siècle era, particularly the decade of Symbolism 1880-1890. In the process of resurrecting of the past, affective memory in Ricœure’s approach turns out to be important, enabling the author to combine autobiography with a testimony about the era in which he was to play an important role alongside masters (Villiers de l’Isle-Adam, Mallarmé…) and (un)famous writers and artists. Thanks to the impressive nature of his writing and discontinuous style, Ajalbert composed a hybrid text in which he included fragments of letters, symbolist poems and his own works. The author’s desire to create a personal myth at the intersection of aesthetics allowed him to show non-obvious connections between symbolism and naturalism.